Translation reception of the reformist novel «Put Yourself in His Place» by Ch. Reade in Russia (1860–70); Лингвистические и культурологические аспекты современного инженерного образования - Сумцова О. В. Ольга Витальевна (2023, 2023)
Based on the comparative analysis of the reformist novel «Put Yourself in His Place» (1869–1870), written by Charles Reade, the famous English writer of the second half of the XIX century, and its Russian translation (Postav’ sebya na ego mesto, 1869–1870), the present article examines the translated reception of this novel in Russia. The focus is on the genre aspects of reception